Sortons du ghetto Histoire politique des homosexualités en Suisse, 1950-1990 - Delessert, Thierry (Gender Issues, 2021)
This book reveals little-known facets on the history of homosexuality in Switzerland. It is based on a detailed analysis of the revision of criminal law in sexual matters, the discourse of groups of key actors (lawyers, police officers, psychiatrists, theologians, homosexuals), as well as the influences of debates in the United States, Germany and France between the end of the Second World War and the 1990s.